The Correlation between Degree of Hypertension and Recurrence Frequency in Hypertension Patients - Chrisinta Yuli Rahmawati; Achmad Kusyairi; Mariani (KHD Production, 2025)
Hypertension or high blood pressure is one of the significant health problems worldwide as it can cause deadly heart disease and stroke that often go unnoticed. Controlling blood pressure is important to prevent the recurrence of hypertension and minimize the occurrence of complications resulting from the condition. This study aims to determine the relationship between hypertension severity and recurrence frequency in hypertensive patients at Senduro Health Center. This study is survey research with a correlational design, utilizing a cross-sectional approach with a population of 80 hypertensive patients in the working area of Senduro Health Center. The sampling technique used was purposive sampling, with a sample size of 65 participants. Data was collected using a sphygmomanometer and a questionnaire on the frequency of recurrence, and data analysis was done using the Spearman Rank test. The study results showed that the most common severity of hypertension was stage 1 hypertension, with 27 respondents (41.5%), and the most common frequency of recurrence was rare recurrence, with 32 respondents (49.2%). There was a significant correlation between the severity of hypertension and the frequency of recurrence in hypertensive patients, with a p-value of 0.000 < α=0.05. The higher the severity of hypertension, the more frequent the recurrence in hypertensive patients at Senduro Health Center. It is hoped that the community can control their blood pressure to minimize recurrence and reduce the risk of complications.